Rapidly Progressive Glomerulonephritis Associated with Systemic Lupus Erythematosus - Jastrzębska K; Gozdowska J; Perkowska-Ptasińska A; Durlik M (Archives of Clinical Nephrology - Peertechz Publications, 2016)
Lupus nephritis is a frequent manifestation of multisystem autoimmune disease - Systemic Lupus Erythematosus and a significant cause of both acute renal injury and the end stage renal disease. Renal involvement is observed in approximately 60% of patients with SLE. We report a case of crescentic glomerulonephritis in a previously healthy 21-year old man who showed signs of insidious symptoms (lower limbs and facial mild edema) in February 2011 and within a brief period developed such clinical features as fever, nausea, vomiting, headache, loin pain, hematuria, oliguria and hypertension. Rapidly worsening renal function became an important  determinant of renal failure therefore hemodialysis therapy was introduced. Conducted immunological tests showed an elevated level of antinuclear antibodies and antibodies to dsDNA as well as low complement (C3, C4) levels. The diagnosis of rapidly progressive glomerulonephritis in the background of diffuse glomerulonephritis with crescent formation was confirmed by the presence of pathological features in a renal biopsy. In addition to hemodialysis, treatment with steroids (methylprednisolone)  and immunosuppressive agents (cyclophosphamide) was applied.The therapy resulted in slow but successful clinical improvement. After two months of treatment there was a recovery of renal function and the patient became dialysis independent. Maintenance therapy has been continued for about 4 years. The serum creatinine level is about 1.2 mg/dL, without proteinuria. Crescentic glomerulonephritis in the course of SLE correlated with unfavorable prognosis and therefore must be treated promptly to prevent irreversible kidney injury. This case illustrates the potential of long-term high-dose immunotherapy in the treatment of RPGN in the course of SLE.